PROSES PENGELOLAAN DANCESPORT DI LOKA ART STUDIO MELALU PENDEKATAN DESIGN THINKING - Pribadi, Scholastica Wahyu (LPPM STIE Muhammadiah Bandung, 2023)
Loka Art Studio is a performing arts company in Gunungkidul. The gap is the relatively high price must be paid in undergoing dancesport training, and the existence of the Loka Art Studio as a light of achievement for students and parents. Research focus on the process of managing the Loka Art Studio with design thinking. The purpose is to find out the management of the Art Studio Workshop in a design-thinking save dancesport. This study uses a qualitative-descriptive method that develops the concept of designing thinking with 5 indicators: empathize, define, ideate, prototype, and test. Primary data from interviews and secondary data from various relevant literature from research journals, books, theses, and other relevant research. In the data collection technique, interviews were carried out using snowball sampling and total 4 subjects. The results are first, empathize, the socio-economic status of students is different and the training process is generally expensive, so it makes parents have limitations. Second, define, Loka Art Studio makes a deeper analysis of why parents experience problems and the expectations of athlete parents in wanting to improve performance. Third, ideate, discussing ideas in order to be able to meet consumer needs and increase parents' interest in enrolling their children as athletes and being part of the art studio organization. Fourth, prototype, the Local Art Studio company makes a product scheme that will be sold. Fifth, test, the Loka Art Studio trials in the form of promotional posters, catalogs, and notification letters to schools regarding product schemes.